Textual thresholds in the Deewan (Alienation and Expatriation) by Hashem Saleh Manna - Thana Hussain Aldhafeeri (IJAS: Indonesian Journal of Arabic Studies, 2023)
Purpose: The objective of this research is to define the concept of textual thresholds, as well as their types and functions, before elucidating the most significant external and internal thresholds in Hashem Saleh Manna's Diwan. Design/ methods/approach: This research was conducted using an analytical descriptive method using a content analysis approach with The primary research source is Hashem Saleh Manna's Dīwān (ālġarabaẗ wā al iġtirāb). Findings: This study found that the thresholds of the text are all that surround it, from the title and its color hues to the author's name, sexual indicators, and dedication to the introduction, which opens the door for the reader to dive into the text and reveal its aesthetics. The title is the book's first boundary, allowing the reader to access the text and discover its many dimensions. Hashim Manna's Deewan's beauty is enhanced by the textual threshold, which encourages readers to explore the text's meanings. And the repetitions (questions and exclamations) in these poems in Deewan demonstrate the instability of the psychological state, the poet's numerous queries, his rejection of his reality, which is forced, and his sentiments of alienation and estrangement. The poet helps the addressee feel his dejection (alienation and estrangement) by expressing his emotions. As in other deewan poems, the poet closes his poem with a house where he prays for Muhammad (Pbuh).تكمن أهمية البحث كونه يتناول فكرة العتبات النصية في ديوان شعري لشاعر مُعاصر، والكشف عن توظيف هذه العتبات في الجانب الدلالي. ويهدف البحث إلى تحديد مفهوم العتبات النصية وأنواعها ووظائفها، ثم بيان أهم هذه العتبات الخارجية والداخلية في ديوان (الغربة والاغتراب) لهاشم صالح مناع، والوقوف على بعض قصائد هذا الديوانلدراسة عتباتها ودلالاتها.ويعتمد البحث على المنهج الوصفي التحليلي من خلال اختيار ديوان (الغربة والاغتراب)، ثم تحليل العتبات النصية فيه. وتوصل الباحث إلى مجموعة من النتائج أهمها: العتبات النصية هي كل ما يحيط بالنص من عناوين وألوان، واسم الكاتب، والمؤشر الجنسي، والإهداء والاستهلال فهي تفتح الأبواب أمام المتلقين للغوص في النص والكشف عن جمالياته، ويعد العنوان العتبة الاستهلالية الأولى للكتاب فهو السبيل للوصول إلى النص، ويُمكن القارئ من تكوين فهمه الخاص للنص واكتشاف أبعاده المختلفة، كما أضافت العتبات النصية إلى ديوان(الغربة والاغتراب) لهاشم مناع جماليات تُحفِّز القارئ إلى التسلل إلى أغوار النص بحثاً عن المعاني المضمرة فيه.